Leaf δ^13 C reflects ecosystem patterns and responses of alpine plants to the environments on the Tibetan Plateau - Song, Minghua; Duan, Deyu; Chen, Hui; Hu, Qiwu; Zhang, Feng; Xu, Xingliang; Tian, Yuqiang; Ouyang, Hua; Peng, Changhui (Ecography, 2008)
Leaf δ 13 C is an indicator of water‐use efficiency and provides useful information on the carbon and water balance of plants over longer periods. Variation in leaf δ 13 C between or within species is determined by plant physiological characteristics and environmental factors. We hypothesized that variation in leaf δ 13 C values among dominant species reflected ecosystem patterns controlled by large‐scale environmental gradients, and that within‐species variation indicates plant adaptability to environmental conditions. To test these hypotheses, we collected leaves of dominant species from six ecosystems across a horizontal vegetation transect on the Tibetan Plateau, as well as leaves of Kobresia pygmaea (herbaceous) throughout its distribution and leaves of two coniferous tree species ( Picea crassifolia, Abies fabri ) along an elevation gradient throughout their distribution in the Qilian Mountains and Gongga Mountains, respectively. Leaf δ 13 C of dominant species in the six ecosystems differed significantly, with values for evergreen coniferous<evergreen broadleaved tree<alpine shrub<sedges∼graminoid<xeromorphs. Leaf δ 13 C values of the dominant species and of K. pygmaea were negatively correlated with annual precipitation along a water gradient, but leaf δ 13 C of A. fabri was not significantly correlated with precipitation in habitats without water‐stress. This confirms that variation of δ 13 C between or within species reflects plant responses to environmental conditions. Leaf δ 13 C of the dominant species also reflected water patterns on the Tibetan Plateau, providing evidence that precipitation plays a primary role in controlling ecosystem changes from southeast to northwest on the Tibetan Plateau.